Effects of physical parameters and chemical dispersant on the formation of oil-particle aggregates (OPAs) in marine environments. (November 2019) - Yu, Yue; Qi, Zhixin; Li, Wenxin; Fu, Sinan; Yu, Xinping; Xiong, Deqi
Abstract: Floating oil and sediments can interact to form oil-particle aggregates (OPAs) in marine environments. Laboratory batch experiments were conducted to investigate the effects of the concentration and size of sediment, temperature, oil types and chemical dispersant on the formation of OPAs. The results showed that the mass of OPAs and oil-particle aggregation rate are mainly related to the sediment concentration. Under the same mass concentration, more oil droplets can be trapped by smaller particles. Nevertheless, larger particles tend to interact more quickly with oil droplets. The effect of temperature on the formation of OPAs is substantially attributed to its influence on oil viscosity, and there is a threshold for oil viscosity which will bring about the maximum OPAs. Spilled oil with a high asphaltene can interact more effectively with the sediments. Appropriate addition of chemical dispersant is favorable for the formation of OPAs while excess addition will inhibit it. Graphical abstract: Unlabelled Image Highlights: Particle concentration affects the aggregation rate and oil trapping efficiency. Smaller particles trap more oil droplets, while larger ones aggregate more quickly. Temperature dominates the formation of OPAs by its influence on oil viscosity. Spilled oil with a high asphaltene can interact more effectively with the sediments. Appropriate addition of chemical dispersant is favorable for the formation of OPAs.